2015
DOI: 10.1002/pssb.201552231
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation characteristic of Fe-based bulk metallic glass laser weld

Abstract: wirginia.pilarczyk@polsl.pl, Phone: þ48 32 237 1234, Fax: þ48 32 237 2281Fe-based bulk metallic glasses are characterized by good magnetic properties, high mechanical strength, and corrosion resistance. Although, despite these properties, their use is limited because of the small sample thickness that could be achieved by rapid solidification. Therefore, one of the most prominent and promising engineering processes which can be used for extending the amorphous materials' application is laser beam welding. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The tests concerning the FZ revealed slightly corrugated surface. The Zr-based alloys did not contain characteristic and clearly visible single convexities, frequently seen in the HAZ of Fe-based alloys [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tests concerning the FZ revealed slightly corrugated surface. The Zr-based alloys did not contain characteristic and clearly visible single convexities, frequently seen in the HAZ of Fe-based alloys [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors attributed the foregoing to the presence of very small crystallite or cracks in the above-named areas and ascribed the test result to the refinement degree and the number of micro-particles. Mechanical properties of materials composed of at least two phases are strictly related to the size distribution or the volumetric content of precipitated reinforcement [ 26 ]. It was ascertained that crystallization or precipitates in the amorphous matrix led to a significant increase in the material hardness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material continuity can be ensured by the proper making of imperfection-free welds. Research [5][6][7][8] revealed that the satisfaction of the * corresponding author; e-mail: wirginia.pilarczyk@polsl.pl condition concerning structural, chemical and propertiesrelated homogeneity proves extremely difficult in terms of BMGs. The difference between the properties of the joint and those of the parent material (PM) indicates the quality of the welding process and is related to the notion of material weldability.…”
Section: Welding Of Amorphous Materialsmentioning
confidence: 99%
“…Particularly for BMGs, the metastable nature and resulting incompatibility with conventional processing and joining methods have become stumbling blocks for their practical applications 7, 8 . To address the ability to join BMGs, various techniques that have been developed specifically or tailored for BMGs based on liquid-state processing including electron beam welding 9, 10 , laser beam welding 11, 12 , gas tungsten arc (GTA) welding 13 , and pulse current method 14, 15 ; or solid-state processing including friction welding 16, 17 , explosion welding 18 , ultrasonic welding 19, 20 , diffusion bonding 21 , spark welding 22 , and resistance spot welding 23 . Recently, a thermoplastic-based method 24 and a liquid-solid joining method 7 were introduced.…”
Section: Introductionmentioning
confidence: 99%